Effects of an integrative nursing intervention on pain in critically ill patients: a pilot clinical trial - Papathanassoglou, Elizabeth; Hadjibalassi, Maria; Miltiadous, Panagiota; Lambrinou, Ekaterini; Papastavrou, Evridiki; Paikousis, Lefkios; Kyprianou, Theodoros (My University, 2018)
Background Pain, a persistent problem in critically ill patients, adversely affects outcomes. Despite recommendations, no evidence-based nonpharmacological approaches for pain treatment in critically ill patients have been developed. Objectives To investigate the effects of a multimodal integrative intervention on the incidence of pain and on secondary outcomes: intensity of pain, hemodynamic indices (systolic and mean arterial pressure, heart rate), anxiety, fear, relaxation, optimism, and sleep quality. Methods A randomized, controlled, double-blinded repeated-measures trial with predetermined eligibility criteria was conducted. The intervention included relaxation, guided imagery, moderate pressure massage, and listening to music. The primary outcome was incidence of pain (score on Critical Care Pain Observation Tool > 2). Other outcomes included pain ratings, hemodynamic measurements, self-reported psychological outcomes, and quality of sleep. Repeated-measures models with adjustments (baseline levels, confounders) were used. Results Among the 60 randomized critically ill adults in the sample, the intervention group experienced significant decreases in the incidence (P = .003) and ratings of pain (P < .001). Adjusted models revealed a significant trend for lower incidence (P = .002) and ratings (P < .001) of pain, systolic arterial pressure (P < .001), anxiety (P = .01), and improved quality of sleep (P = .02). Conclusion A multimodal integrative intervention may be effective in decreasing pain and improving painrelated outcomes in critically ill patients. (American Journal of Critical Care. 2018; 27:172-185).
Keywords: Multimodal integrative intervention; Incidence of pain; Mean arterial pressure; Quality of sleep